2020
DOI: 10.1016/j.arcmed.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Biomarkers Predicting COVID-19 Severity in the Emergency Room

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 6 publications
(4 reference statements)
3
28
0
2
Order By: Relevance
“…A low oxygen saturation (SaO 2 ) is one of the main criteria for the de nition of a severe case. SaO 2 was found as another candidate marker of progressive severity 28 and also validated in the present study. We comprehensively investigated the relationship between risk factors and the severity of COVID-19 and rst concluded that the integration of NLR with SaO 2 may lead to improved prediction.…”
Section: Discussionsupporting
confidence: 82%
“…A low oxygen saturation (SaO 2 ) is one of the main criteria for the de nition of a severe case. SaO 2 was found as another candidate marker of progressive severity 28 and also validated in the present study. We comprehensively investigated the relationship between risk factors and the severity of COVID-19 and rst concluded that the integration of NLR with SaO 2 may lead to improved prediction.…”
Section: Discussionsupporting
confidence: 82%
“…We suggest that the following diagnostic screenings may be appropriately considered during COVID-19 era for patients presenting with the aforementioned symptoms and history: respiratory rate, natriuretic peptides, lymphocyte count, C-reactive protein, D-dimer, fibrinogen, electrocardiogram, and chest X-ray. Analysis of the arterial blood gas could be performed as an additional test to identify the culprit behind the patient's destabilization [12]. Additionally, lung ultrasound could be used as an alternative method to discern a pulmonary lesion associated with interstitial pneumonia or increased comet related to water content [13].…”
Section: Diagnostic Tests and Screening In Patients With Acute Dyspneamentioning
confidence: 99%
“…Chen C et al 2020 -----0,001 --<0,001 -<0, Atualmente, sabe-se que a COVID-19 pode provocar manifestações clínicas heterogêneas, das quais, ampliam-se uma gama de espectros clínicos, desde uma condição Research, Society andDevelopment, v. 9, n. 11, e2619118955, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.8955 assintomática até uma Síndrome Respiratória Aguda (SRA) com risco de óbito (Assandri et al, 2020). Novas cepas de coronavírus com mutações surgiram ao longo dos anos e vem sendo associadas a fatores de virulência aumentados, causando altas taxas de mortalidade entre a população.…”
Section: Valor De P=005 (Pacientes Graves E Não Graves)unclassified
“…Estudos preliminares vêm revelando que testes laboratoriais podem se apresentar alterados em pacientes com a COVID-19 sendo, portanto, indicado como uma alternativa rápida e sensível para a observação e identificação desta doença. O RT-PCR ainda é o teste ouro padrão para diagnóstico, entretanto, outros exames complementares têm sido associados às observações de prognósticos (Assandri et al, 2020). Sendo assim, este artigo de revisão abordou parâmetros laboratoriais associados às características de gravidade de pacientes com COVID-19.…”
Section: Valor De P=005 (Pacientes Graves E Não Graves)unclassified